The Two-Sided Effect of Leader Unethical Pro-organizational Behaviors on Subordinates’ Behaviors: A Mediated Moderation Model - Wen, Peng; Chen, Cheng; Chen, Silu; Cao, Yuyang (Frontiers in Psychology, 2020)
Research suggests that unethical pro-organizational behavior (UPB) has two conflicting characteristics: unethical and pro-organizational. However, little attention has been paid to the negative and positive outcomes of UPB. Therefore, the present study aimed to fill this gap by examining a mediated moderation model on the effects of leader UPB on their subordinates’ behaviors. Based on social information processing theory and three-wave survey data from 204 supervisor-subordinate dyads in China, we found that the mixed relationships between leader UPB and subordinates’ behaviors were dependent on the leader’s Machiavellianism. Specifically, for high Machiavellian leaders, their UPB was positively related to subordinates’ unethical behaviors via subordinates’ moral disengagement. For low Machiavellian leaders, their UPB was positively related to subordinates’ organizational citizenship behaviors via their organizational identification. The theoretical contributions and practical implications of the findings are discussed.